Manipulation of probiotics fermentation of milk by Cinnamon Zeylanicum, Glycyrrhiza glabra or Allium Sativum and their effects on inhibition of Helicobacter Pylori growth In Vitro / Sara Behrad - Behrad, Sara (2011)
Dairy products containing probiotics (e.g. Lactobacillus ssp. and Bifidobacterium) and certain herbs have inhibitory effects on the growth of Helicobacter pylori. The objectives of the present study were to determine the effects of herbs traditionally used for the treatment of gastric ulcer on yogurt fermentation characteristics, probiotic bacteria and the growth of H. pylori in vitro. Cinnamon zeylanicum (cinnamon), Glycyrrhiza glabra (licorice) or Allium sativum (garlic) was individually mixed with milk and the mixtures were fermented by probiotic bacteria to form herbal-yogurts. Changes in pH, titratable acididity, anti oxidant activity and the viable cell count of Lactobacillus ssp. and Streptococcus thermophilus were evaluated during refrigerated storage. The in vitro inhibition of H. pylori growth was determined using agar diffusion and minimum inhibitory concentration (MIC) methods. There were no significant differences in pH and TA between herbal-yogurts and plain-yogurt during fermentation and storage. Refrigeration up to 28 days increased (p>0.05) viable Lactobacillus ssp. counts to 15.8 x 106cfu/ml in the plain-yogurt but the presence of cinnamon, licorice or garlic tend to inhibit the increase (p>0.05) in herbal yogurts. Garlic-yogurt showed the least favored (p>0.05) for all characteristics tested for organoleptic properties. Water extract of cinnamon-yogurt and licorice-yogurt on day 7 of refrigerated storage showed the highest inhibitory effect against H. pylori strains UM-1, UM-2 and UM-3. An MIC of 3ml was effective for all H. pylori isolates by cinnamon and licorice yogurt water extracts, but only for H. pylori isolate UM-3 by garlic yogurt extract. Licorice-yogurt water extract had MIC at 1ml for isolate UM-1 and UM-2, whereas cinnamon-yogurt water extract had MIC at 2ml. Garlic-yogurt water extract had weak inhibition on H. pylori. The present in vitro findings indicate that yogurt and herbs under study can decrease the growth of H. pylori. These herbs could be used as food additives for the production of novel dairy products because of their unique functional attributes and potential mitigation on H. pylori growth.